Identification Lithology of Geothermal Potential Areas Using the Electrical Resistivity Tomography (ERT) Method - Raihana, Hana; Suhendra, Suhendra; Nazli, Khairun; Halauddin, Halauddin; Refrizon, Refrizon (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
The rock lithology of the potential hydrothermal area has been studied using Electrical Resistivity Tomography (ERT) in Pungguk Pedaro Village, Bingin Kuning District, Lebong Regency. Field data acquisition uses a stretch length of 480 meter with the MAE X612-EM Geoelectric tool that forms a straight line. ERT method, using Res2dinvx64 software. The study aims to determine the subsurface conditions of the potential hydrothermal area and the characteristics of the rocks that make up the hydrothermal area. The results of this study can be concluded that Pungguk Pedaro Village is dominated by clay, sandstone, sandy gravel, andesite, basalt, and granite rocks. In this study, measurements were taken with six lines to see variations in resistivity values as a reference for identifying potential geothermal lithologies. There is 1 line that cuts to five lines to validate the resistivity value of each line. Line 1 has no potential for hydrothermal distribution because there has been a mixture of hydrothermal water with mountain water, so this line will only provide groundwater.